Analysis of the sequence of segmental participation during the final movement of the rotational shot put - M. Gutiérrez-Dávila; J. Rojas; J. Campos (Asociación Española de Ciencias del Deporte, 2010)
The general objective of this study is to carry out a descriptive analysis of the general pattern of the segmental participation during the phase of final acceleration of the rotational shot.  Six elite putters have been analyzed in the final of the World Indoor Championship held in Valencia, 2008. Three dimensional photogrammetric techniques (3D) have been used by means of two cameras synchronized temporarily to 100 Hz. The registrations have been normalized in function of the time using the algorithms of splines of fifth grade and being interpolated their values with regard to the percentage of the total time, considering that the time used during the final movement of acceleration of the weight is different for each putter. The results show that the kinetic chain used during the final movement of acceleration of the put has two differentiated models: Until 60% of the total time a push model takes place or of simultaneous participation of the articulations of the ankle, the knee and the hip in extension and, next, the participation pattern is sequential, especially by means of the contribution of the extension of the elbow and wrist. The rotation movement through the vertical axis stays until the take off of the put. Key Words:  kinetic chain, biomechanics, 3D photogrammetric.